Empowering Cadres to Increase Parental Awareness of Tuberculosis (TB) in children Prevention in Pacarkembang District, Surabaya - indriatie, indriatie; Novitasari, Aida; Nur Hasanah (Frontiers in Community Service and Empowerment, 2025)
ABSTRACT. The working area of Pacarkeling Health Center includes Pacarkeling and Pacarkembang villages, Surabaya. The development of health promotion activities at the health center largely involves active community participation through health cadres. Tuberculosis (TB) in children cases in Surabaya remain high, influenced by behavioral and environmental factors. TB is not limited to adults but also affects children, thus requiring comprehensive understanding of the disease, its signs and symptoms, treatment, and prevention. The objectives of this community service program are to assess the understanding of cadres regarding Tuberculosis (TB) in children, assess their knowledge of Tuberculosis (TB) in children prevention; and evaluate their awareness and involvement in counseling and educational activities related to Tuberculosis (TB) in children prevention. The targets and outcomes of the community service program were successfully achieved. The mandatory output for the PKM (Community Service Program) scheme included an increase in cadres’ understanding of Tuberculosis (TB) in children and its prevention at the "good" level—from 90% to 93.3% among 30 cadres. Additionally, among 30 parents, there was an increase in the "sufficient" category of understanding regarding assistance, cadres’ concern in counseling, and the prevention of Tuberculosis (TB) in children —from 13.3% to 20%. As for the publication output, a manuscript was prepared and submitted to the FISCE Journal. In addition, a video documenting the implementation of the activities was uploaded to YouTube and can be accessed via the following link: https://youtu.be/uP537MD5Gcg. The additional outputs included a booklet titled Parental Awareness of Tuberculosis Prevention in School-Aged Children, as well as supporting documentation such as a certificate (ECOO2025113694), a community service activity video, and a copyright certificate (EC002025123468) for a work titled Parental Awareness of Tuberculosis Prevention.